Development of a Pharmacokinetic Model That Accounts for the Plasma Concentrations of Conjugated and Unconjugated Bilirubin Observed in a Variety of Disease States - Levitt DG; Levitt MD (Clinical and Experimental Gastroenterology, 2023)
David G Levitt,1,* Michael D Levitt2,* 1Department of Integrative Biology and Physiology, University of Minnesota, Minneapolis, MN, USA; 2Research Service, Veterans Affairs Medical Center, Minneapolis, MN, USA*These authors contributed equally to this workCorrespondence: David G Levitt, Department of Integrative Biology and Physiology, University of Minnesota, 6-125 Jackson Hall, 321 Church St. S. E, Minneapolis, MN, 55455, USA, Tel +612 594 0272, Email levit001@umn.eduIntroduction: For a large variety of liver pathologies, the plasma unconjugated (UB) and conjugated (CB) bilirubin concentrations appear to be coupled. For example, in alcoholic cirrhosis, UB and CB are roughly the same over a large range of total bilirubin, requiring an initial massive increase (about 40-fold) in plasma CB to reach the level of UB and then similar increases in UB and CB as the disease progresses. This coupling has been either unrecognized or ignored and this paper is the first attempt to try to explain it quantitatively in terms of known hepatic cell metabolic and membrane transport properties.Methods: A simplified pharmacokinetic model is developed and applied to a variety of hyperbilirubinemic pathologies. A central feature of the model is based on the recent observation that double knockout of the rat OATP1A and OATP1B hepatic transporters produces a roughly 400-fold increase in plasma CB, indicating that there is a normal rapid recycling of CB from the cell to the plasma with reuptake via OATP. We use the experimental rat Km of OATP CB transport to show that OATP uptake becomes saturated at relatively low plasma CB concentrations, decreasing uptake, and producing massive (up to 1000-fold) increases in CB in some pathologies. It is assumed that UB and CB are competing for the OATP transporter, producing the increased plasma UB that is observed in “pure” CB pathologies.Results: The model accurately describes the clinically observed UB and CB for pure UB (Gilbert’s, hemolytic anemia) and CB (Dubin-Johnson, Rotor syndrome, biliary atresia) pathologies as well as in cirrhosis.Conclusion: This model is a preliminary, first attempt to quantitatively describe UB and CB pharmacokinetics. It is hoped that it will stimulate more detailed measurements and analysis.Keywords: bilirubin, Dubin-Johnson, Rotor, Gilbert’s, OATP